WOMEN LEADERSHIP, REGIONAL GOVERNMENT INFORMATION SYSTEM AND LOCAL GOVERNMENT FINANCIAL PERFORMANCE IN WAKATOBI REGENCY, INDONESIA - Abdul Syukur; Endar Pituringsih; Ayudia Sokarina (Malete Journal of Accounting and Finance)
This study aims to determine the effect of Women's Leadership (X1), Local Government Information System (SIPD) (X2), and Local Wisdom (Z) as moderating factors on regional financial management performance (Y). Using purposive sampling technique, this study collected data from 102 respondents, which were then analyzed using Partial Least Squares (PLS) method. The results showed that Women's Leadership (X1) and Local Government Information System (SIPD) (X2) significantly affect local government financial performance (Y). However, the interaction between Local Wisdom (Z) and SIPD (X2) does not have a significant effect on local financial performance (Y). In contrast, the interaction between Local Wisdom (Z) and Women's Leadership (X1) showed a significant influence on local government financial performance (Y). Thus, these findings highlight the importance of women's leadership and the moderating influence of local wisdom in the context of local financial management. Local governments should pay attention to the importance of women's leadership in improving local financial management performance, as well as consider local wisdom as a factor that can strengthen the influence of leadership on financial performance.